2017
DOI: 10.2337/db17-0218
|View full text |Cite
|
Sign up to set email alerts
|

Tbx15 Defines a Glycolytic Subpopulation and White Adipocyte Heterogeneity

Abstract: Tbx15 is a member of the T-box gene family of mesodermal developmental genes. We have recently shown that Tbx15 plays a critical role in the formation and metabolic programming of glycolytic myofibers in skeletal muscle. Tbx15 is also differentially expressed among white adipose tissue (WAT) in different body depots. In the current study, using three independent methods, we show that even within a single WAT depot, high Tbx15 expression is restricted to a subset of preadipocytes and mature white adipocytes. Ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
49
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 30 publications
5
49
0
Order By: Relevance
“…Tbx15 mRNA expression, which we previously showed marks a subset of cells in the subcutaneous adipose tissue (Lee et al, 2017a), was~3-fold higher in GFP + preadipocytes derived from the subcutaneous fat of Tagln-cre;Rosa26 mT/mG . Tbx15 mRNA expression, which we previously showed marks a subset of cells in the subcutaneous adipose tissue (Lee et al, 2017a), was~3-fold higher in GFP + preadipocytes derived from the subcutaneous fat of Tagln-cre;Rosa26 mT/mG .…”
Section: Utilizing Lineage Tracing Models To Differentially Label Adimentioning
confidence: 55%
See 3 more Smart Citations
“…Tbx15 mRNA expression, which we previously showed marks a subset of cells in the subcutaneous adipose tissue (Lee et al, 2017a), was~3-fold higher in GFP + preadipocytes derived from the subcutaneous fat of Tagln-cre;Rosa26 mT/mG . Tbx15 mRNA expression, which we previously showed marks a subset of cells in the subcutaneous adipose tissue (Lee et al, 2017a), was~3-fold higher in GFP + preadipocytes derived from the subcutaneous fat of Tagln-cre;Rosa26 mT/mG .…”
Section: Utilizing Lineage Tracing Models To Differentially Label Adimentioning
confidence: 55%
“…The most dramatic differences in gene expression were between Type 1 preadipocytes and the other two groups, as can be visualized by a heatmap of the 50 most differential genes and by principal component analysis (Figs 2D and EV1E), however, significant differences were also present between Types 2 and 3, as visualized by a heatmap of the 50 most differential genes between these two groups ( Fig 2E). C Bright-field image of depot-derived cell lines after in vitro adipogenic differentiation and Oil Red O staining (Lee et al, 2017a). In addition, all three clusters were also able to differentiate into osteoblasts and chondrocytes in vitro using conditions that induce bone and cartilage development (Boquest et al, 2005) as visualized by Alizarin Red S staining of calcium deposition and Alcian Blue of acidic mucins, respectively ( Fig EV1F).…”
Section: Clonal Analysis Of Adipocytes Derived From Immortomouse Tm Amentioning
confidence: 95%
See 2 more Smart Citations
“…T-box protein 15 (Tbx15) regulates adipocyte differentiation and triglyceride accumulation (Gesta et al, 2011) and Gpc4 enhances both insulin receptor signaling and adipocyte differentiation (Ussar et al, 2012). Recently, Lee and colleagues have shown that Tbx15 regulates a switch from oxidative to glycolytic metabolism and marks a glycolytic subpopulation of adipocytes (Lee et al, 2017a). Moreover, Shox2 is highly expressed in cells of flank/psWAT compared with pgWAT, and controls lipolysis rates, orchestrating at least some of the differences between subcutaneous and visceral adipocytes (Lee et al, 2013b).…”
Section: Expression Of Developmental Genes Differs Between Adipose Timentioning
confidence: 99%